IT-related crimes and Bitcoin (Academic Journal of Internal Affairs, 2017)
Focusing on international and Hungarian experiences, the author provides an overview of IT-related crimes and the Bitcoin-phenomenon.
Keywords: IT; crime; Bitcoin